The Role of Aqidah Akhlak Education in Forming Sturdy Aqidah and Moral Al Karimah Students at Tpi Rambung Sialang Private MA - Fadillah, M. Alwi; Gunawan, Ary; Shiddiq, Ahmad (Cattleya Darmaya Fortuna, 2023)
This research raises the issue of the role of learning Akidah Ahklak in Forming a strong Akidah and AkhlakAl-Karimah. The subjects in this study were class XII MAs Tpi Rambung Sialang students in October 2022. This type of research is field research, namely research where data collection is obtained by writing. This research was conducted in Rambung Sialang Village, Sei Rampah District, Serdang Bedagai Regency. However, more specifically, this research was conducted at a school in the village, namely the MAs Tpi Rambung Sialang school. The research subjects were the school principal, deputy principal for curriculum, Akidah Akhlak teachers and students. While the method of data collection that the authors do is observation and interviews. Data collection was carried out by observation, questionnaire, and assignment methods. The results of this study indicate that the learning process at MAs Tpi Rambung Sialang runs quite effectively in accordance with the basic concept of the learning process carried out by educators in general, namely that students follow the learning process enthusiastically in the Akidah Akhlak subject. The learning methods used by the Akidah Akhlak subject teachers at the Tpi Rambung Sialang MAs school include: the lecture method, the discussion method, the question and answer method, assignments. However, the results of observations and observations made in this study were not as expected. Even though the implementation of the Aqidah Akhlak in schools has gone according to plan, the strong character of the aqidah and the alkarimah character of these students are still lacking.